ANALISIS POLA TABUHAN BERUAS PADA MUSIK IRINGAN JEPIN TEMBUNG PANJANG DI KOTA PONTIANAK - Octaviandri Octaviandri; Ismunandar Ismunandar; Asfar Muniir (Universitas Tanjungpura, 2019)
AbstractThis research based on lack of interest in the young generation of art was inherited from ancestors hereditary and it was necessary that there were attempts to learn and preserve the tradition. One of artistic tradition almost extinct and start unknown by communities are musical accompaniment Tari Jepin Tembung Panjang in Pontianak. (The purpose of this research is: 1 ) the descriptive analysis of ‘Tabuhan Beruas’ on music of Jepin Tembung Panjang accompaniment. The methods used in this research was descriptive method analysis.The data analysis used in this research was the result of direct observation and an interview to informants of the music of Jepin Tembung Panjang. Data analyzed qualitatively, with speakers Mohammad Joseph Dahyani and Anwar Djafar who actively involved as well as knowing about the music, tradition especially the music of Jepin Tembung Panjang in Pontianak. Based on the analysis of the data, it can be inferred that the pattern of Jepin Tembung Panjang was the result of repeated of literal hornets from one pattern.Keywords: Analysis, Jepin, Pola Tabuhan, Pontianak, Tembung Panjang